Influence of different levels of pressmud compost and fertilizer grades on growth, yield and quality of soybean (Glycine max): Influence of different levels of pressmud compost and fertilizer grades on growth, yield and quality of soybean (Glycine max) - GORE VARSHARANI SHIVAJI,; N K KALEGORE, (Journal of Oilseeds Research, 2020)
Pressmud, a by-product of sugar industry and is left behind as a by-product. In the present investigation, the effect of pressmud, supplemented at three different levels of fertilizers, on soybean crop was taken up through a field experiment. The results indicated that the growth, yield and quality attributes of soybean were significantly influenced by different levels of pressmud compost and fertilizer grades.